Challenges of quantity surveyors in Klang Valley to work from home - Chew, Boon Han; Md Noh, Nur Ilya Farhana; Lee, Jin Chaic; Ahmad, Zakiah; Ng, Jing Lin; Surol, Salihah; Syamsunur, Deprizon; Al-Mansob, Ramez; Razman, Ruzaimah (UKM PRESS, 2022)
With the uprising trend of modern management systems adoption, the enthusiasm for corporates to exercise the working culture of work from home are seemingly proliferated to fit in the recent corporate world. However, the published research papers and statistics regarding the information and comprehension of quantity surveyor to work from home are unexpectedly sporadic. Therefore, this research reviews the insights of quantity surveyor to work from home while drawing discussion and conclusion on the uprising challenges of work from home for quantity surveyors to execute their roles. The paper compiles the responses obtained from the methodology of surveying 145 related professions in construction industry around Klang Valley area. The questionnaire was designed with five-point Likert scale, and the data was analyzed by using SPSS software. The study displayed reduced supervision and direction as the greatest challenge, followed by significant challenges which include communication and coordination challenges, organization performance and productivity, job performance and productivity, and unclear performance metrics. Hence, personnel in the industry should be aware of the potential challenges of a quantity surveyor to work from home due to their roles, in order to indicate the potential effects that may incur to the individual and organization.